ANALISIS BIFURKASI MODEL PERTUMBUHAN TUMOR DENGAN PERSAMAAN LOGISTIK WAKTU TUNDA - Dewi, Febriana; sutimin, sutimin (MATEMATIKA, 2011)
ï»¿ï»¿ï»¿ï»¿ï»¿In this paper is being studied about the logistic tumor growth model with time delay. The mathematical model is in non-linear differential equation with time delay difficult to find the solution analytically, so here we analyze the behavior of the model through perturbation. The tumor growth model has two equilibriums (i.e.at and ). Because this growth model is non-linear hence to analyze the stability of each equilibrium point is done through the linearization method. By using a perturbation procedure, the equilibrium point is unstable and is stable. The equilibrium is stable for , unstable for Â and Hopf bifurcation occurs at .